Kemitraan Pengembangan Sektor Pariwisata (Studi Kasus: Bali Elephant Camp, Desa Wisata Carangsari, Kecamatan Petang, Kabupaten Badung) - Pebriani, Ni Kadek Dwi; Erviantono, Tedi; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2017)
ABSTRACT The Government must work harder to develop the Tourism Departement in North Badung due to inequality of tourism development with the South Badung, although this region has many abundant natural resources. For example the Bali Elephant Camp which is an icon of the Carangsari Tourism Village, Petang District. Based on the development of tourism system in the Petang District that involves cross-sectoral from government, the private sector and the public. Then we need to review about the tourism development’s partnership. The problem underlying this study is the lack of attention of the government due to infrastructure development of the attraction and other supporting facilities to increase this Tourism Village. The method used in this research is Qualitative Descriptive research methods. This study was conducted to determine how the partnership development of tourism sector in Bali Elephant Camp guided by the three principles of partnership, there are : Equity, Transparancy and Mutual Benefit. The results of this study indicate that the partnership made between the government, private sector and communities in the development of tourism in Bali Elephant Camp just by Equity and Mutual Benefit principle, while the Transparancy principle still not optimal. The partnership during this time do not have any form but according to the kinship principle in the course of the partnership. There was no contract between the government and the private sector is currently run partnership for the partnership in the sphere of small, but there is different to the community partnership that use employment contract because it involves the lease of land.. Keywords: Partnership, Tourism Development, Tourism Village